2022
DOI: 10.1126/sciimmunol.abh3816
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gut microbiome–induced IgG regulates neonatal gut microbiome and immunity

Abstract: The gut microbiome elicits antigen-specific immunoglobulin G (IgG) at steady state that cross-reacts to pathogens to confer protection against systemic infection. The role of gut microbiome–specific IgG antibodies in the development of the gut microbiome and immunity against enteric pathogens in early life, however, remains largely undefined. In this study, we show that gut microbiome–induced maternal IgG is transferred to the neonatal intestine through maternal milk via the neonatal Fc receptor and directly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
2
16
1
Order By: Relevance
“…The immunity of a neonate is poorly developed and as such may not be competent in fighting against the polymicrobial organisms associated with FG. 12,13,14 There are epigenetic regulation of pediatric and neonatal immune systems which may account for the relative immunosuppression. 12 The median age of Fournier's gangrene in this study is 14days.…”
Section: Discussionmentioning
confidence: 99%
“…The immunity of a neonate is poorly developed and as such may not be competent in fighting against the polymicrobial organisms associated with FG. 12,13,14 There are epigenetic regulation of pediatric and neonatal immune systems which may account for the relative immunosuppression. 12 The median age of Fournier's gangrene in this study is 14days.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of placental IgG transfer occurs after 28 weeks of gestation. IgG levels reach 50% maternal concentration between 28 and 33 weeks gestation and will rise above maternal levels by 20%–30% at term ( 43 , 44 ). It is possible that low IgG levels in preterm infants may predispose these infants to develop NEC.…”
Section: Immunological Status Of Infants With Necmentioning
confidence: 99%
“…We also found that serum IgG was decreased in cluster 1 compared to that in cluster 2. As the most abundant serum immunoglobulin, IgG is conventionally linked to systemic infection because its induction requires the crossing of the barrier by antigens ( 34 36 ). High IgG immune responses generally occur during some specific disease status, such as in inflammatory bowel disease, in which the intestinal barrier is disrupted and pathogenic microorganisms translocate from the lumen ( 37 39 ).…”
Section: Disscusionmentioning
confidence: 99%